The choice of anode material for the electrochemical synthesis of peroxyacetic acid - Bilous, T. A.; Tulskaya, A. G.; Matrunchyk, O. L. (Kyiv National University of Technologies and Design, 2017)
A high-purity peroxyacetic acid may be produced electrochemically. The kinetics of anodic processes at electrolysis of acetic acid water solutions have been studied with application of different kinds of anodic materials. It has been shown that the formation of peroxyacetic acid is possible when the anodic potential is above 2,0 V. The choice of lead dioxide plated on titanium current-lead was justified. Application of lead dioxide in the electrochemical synthesis of peroxyacetic acid allows to increase the current output up by 8-12 % comparing to platinum.
Keywords: peroxyacetic acid; platinum anode; lead-dioxide anode; anodic process